Modelling the influence of climate on malaria occurrence in Chimoio Municipality, Mozambique - Ferrão, João Luís (2017)
Ferrão, J. L., Mendes, J. M., & Painho, M. (2017). Modelling the influence of climate on malaria occurrence in Chimoio Municipality, Mozambique. Parasites and Vectors, 10(1), 1-12. DOI: 10.1186/s13071-017-2205-6